Evaluating SARS-CoV-2 Spike Protein Transfection in HEK-293T Cells for VLP Applications - Rohmah, Ilmiana Nurur; Hafil Kusuma, Kavana; Ika Christina, Yuyun; Rizqi Dwijayanti, Dinia; Mustikaningtyas, Dewi; Widodo, Nashi; Sasmito Djati, Muhammad (The Journal of Experimental Life Science, 2024)
The spike protein in SARS-CoV-2 works mainly to initiate infections, especially for binding to host cells and fusing with cell membranes. Characterizing SARS-CoV-2 spikes protein transfection cells could optimize the production of VLP in HEK-293T cells. Therefore, the present study aimed to investigate the characteristics of SARS-CoV-2 spike protein expression in transfected HEK-293T cells. Characterization of spike protein in transfected-HEK 293T cells was used to determine VLP formation in SARS-CoV-2. The study was conducted by isolating DNA and protein from transfected HEK 293T cells and analyzing spike expression using Polymerase Chain Reaction (PCR) and Flow Cytometry. The success of the SARS-CoV-2 spike protein transfection in PCR analysis has yet to be confirmed because DNA band smears do not specifically indicate the spike protein's size. However, the SARS-CoV-2 spike protein was successfully confirmed using flow cytometry with the percentage of spike-EGFP by 30%. Therefore, the present study confirmed the presence of spike protein in transfected HEK 293T cells by flow cytometry analysis. Keywords: Coronavirus, Characterization, DNA, Spike, Virus-Like Particle (VLP)